2022
DOI: 10.3390/jcm11247343
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Glove Digital System Promotes Restoration of Upper Limb Motor Function and Enhances Cortical Hemodynamic Changes in Subacute Stroke Patients with Mild to Moderate Weakness: A Randomized Controlled Trial

Abstract: This study was a randomized controlled trial to examine the effects of the RAPAEL® Smart Glove digital training system on upper extremity function and cortical hemodynamic changes in subacute stroke patients. Of 48 patients, 20 experimental and 16 controls completed the study. In addition to conventional occupational therapy (OT), the experimental group received game-based digital hand motor training with the RAPAEL® Smart Glove digital system, while the control group received extra OT for 30 min. The Fugl-Mey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In subgroup analyses, patients who had reached chronic stroke status (latency >6 months) showed significant improvement in their FMA-UE score (MD 4.93, 95% CI: 0.93~8.93, I 2 = 19%), with those whose stroke latency was less than six months also showing significant improvement (MD 8.84, 95% CI: 4.47~13.22, I 2 = 0%). The three trials [ 15 , 17 , 19 ] which used the RAPAEL Smart Glove revealed significant improvement in FMA-UE scores (MD 8.43, 95% CI: 4.27~12.59, I 2 = 0%), as did the other four studies which involved other devices (MD 5.29, 95% CI: 0.90~9.67, I 2 = 27%). In the subgroup involving a training length of less than 30 min, significant improvement in FMA-UE scores was found (MD 5.85, 95% CI: 2.49~9.21, I 2 = 15%), with those trials whose training length was more than 30 min also showing significant improvement (MD 9.01, 95% CI: 2.77~15.26, I 2 = 3%).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…In subgroup analyses, patients who had reached chronic stroke status (latency >6 months) showed significant improvement in their FMA-UE score (MD 4.93, 95% CI: 0.93~8.93, I 2 = 19%), with those whose stroke latency was less than six months also showing significant improvement (MD 8.84, 95% CI: 4.47~13.22, I 2 = 0%). The three trials [ 15 , 17 , 19 ] which used the RAPAEL Smart Glove revealed significant improvement in FMA-UE scores (MD 8.43, 95% CI: 4.27~12.59, I 2 = 0%), as did the other four studies which involved other devices (MD 5.29, 95% CI: 0.90~9.67, I 2 = 27%). In the subgroup involving a training length of less than 30 min, significant improvement in FMA-UE scores was found (MD 5.85, 95% CI: 2.49~9.21, I 2 = 15%), with those trials whose training length was more than 30 min also showing significant improvement (MD 9.01, 95% CI: 2.77~15.26, I 2 = 3%).…”
Section: Resultsmentioning
confidence: 88%
“…After primary screening we identified 156 articles for use in our full-text assessment. Ultimately, eight studies were incorporated into our analysis involving a total of 309 participants after assessment for eligibility [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The flowchart of the selection procedure is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations